Necrotizing enterocolitis in haemolytic disease of the newborn: a retrospective cohort study. Issue 2 (19th December 2019) - Ree, Isabelle M.C.; de Grauw, Anne M.; Bekker, Vincent; de Haas, Masja; te Pas, Arjan B.; Oepkes, Dick; Middeldorp, Annemieke (J.) M.; Lopriore, Enrico
Abstract : Background and objectives: Necrotizing enterocolitis (NEC) is a common and often severe gastrointestinal emergency in newborn infants. While usually affecting (very) premature infants, an association between NEC and haemolytic disease of the foetus and newborn (HDFN) has been suggested. HDFN may be an additional risk factor to develop NEC. The objective of this study was to evaluate the occurrence of NEC in infants affected with moderate to severe HDFN in a large single centre cohort as compared to a broad population of infants without HDFN. Materials and methods: Retrospective cohort study of medical records of neonates with and without HDFN, with a gestational age at birth ≥30 weeks and ≤38 weeks, and admitted to the Leiden University Medical Center between January 2000 and December 2016. Results: A total of 3284 patient records of infants born in the study period were reviewed and 317 cases of HDFN were identified. The incidence of NEC was significantly higher among infants with HDFN compared to infants without HDFN: 4/317 affected infants (1·3%) vs. 11/2967 affected infants (0·4%, relative risk 3·40, 95% confidence interval: 1·09–10·63). Conclusions: We observed a higher incidence of NEC in an overall late preterm to near term population of infants with moderate to severe HDFN, compared to infants born without HDFN. The clinician taking care of an HDFN‐affected infant should be cautious of this higher risk.